An evaluation of the integrated sustainable rural development programme highlighting stakeholder mobilisation and engagement - Kirsten, Johann F. (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Rural Development Planning))--University of Pretoria, 2007.